Depressive Symptoms, Lack of Physical Activity, and Their Combination Towards Health Care Utilisation Frequency - Haider, Sandra (Int J Environ Res Public Health, 2019)
Depressive symptoms and lack of physical activity are independent factors that lead to higher health care utilisation, often occurring simultaneously. We aimed to assess the effects of depressive symptoms, lack of aerobic physical activity (PA), and the combination of those factors on the probability of using in- and outpatient health care services in men and women. Data from 15,770 people from the nationally representative Austrian Health Interview Survey (AT-HIS) were used. In analysis, depressive symptoms, adjusted for sociodemographic, health related, and lifestyle-related factors were associated with higher odds of outpatient health care utilisation (OR: 1.60; 95% CI: 1.19–2.14) in men and (OR: 2.10; 95%CI: 1.65–2.66) in women, and with higher odds of inpatient health care utilisation (OR: 1.52; 95% CI: 1.09–2.10) in men and (OR: 2.09; 95% CI: 1.64–2.68) in women. However, depressive symptoms were not associated with higher health care utilisation in the fully adjusted models. In men, co-existence of depressive symptoms and lack of health enhancing physical activity (HEPA) was associated with higher odds of using inpatient health care services, compared to the presence of only one or none of the factors. In conclusion, our results show that depressive symptoms are associated with more health care utilisation in both men and women and that the co-existence of both depressive symptoms and lack of HEPA elevated the odds for inpatient health care utilisation in men even more.